Development of Carbon Pricing Policies for Creating a Low-Carbon Economy: A Systematic Literature Review Using PRISMA - Ranteala, Anisa Oktaviani; Firdaus, Rifqi Ihsan; Nur, Mohamad Ichsana (Department of Public Administration, 2024)
This article discusses the development of carbon pricing as a strategy to create a low-carbon economy. Carbon pricing is defined as an economic policy that imposes a cost on CO2 emissions, with several countries, including Japan and Indonesia, having implemented related regulations. The study employs a Systematic Literature Review (SLR) approach using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology. Challenges in implementing carbon pricing include economic distribution issues, political resistance, and the need for international policy harmonization. Given the urgency of addressing climate change, carbon pricing is a crucial policy instrument for transitioning to a low-carbon economy and achieving environmental sustainability. Special support for industries and vulnerable populations, as well as monitoring and evaluating the impact of the policy, is essential to ensure the effectiveness and fairness of carbon pricing strategies.